Room temperature wear characteristics of Al-Si-Cd bearing alloys - Pathak J.P.; Karimi D.; Tiwari S.N. (My University, 2025)
The aim of the present work is to assess the behaviour of aluminium-silicon-cadmium bearing alloys, particularly the role of cadmium as a solid lubricant during wear testing at room temperature. Compositions of Al-Si-Cd alloy containing 3 wt.% and 5 wt.% silicon and 1-5 wt.% cadmium were prepared by a special plunging and stirring technique. Wear characteristics of as-cast alloy were studied under dry sliding conditions at a relative humidity of about 68% and an ambient temperature of 304 K. The wear volume was measured as a function of sliding distance, applied load, sliding velocity and alloy compositions by using a pin-on-disc wear test machine. Optical microscopy of wear debris and scanning electron microscopy of worn test pin surfaces revealed the interaction of the debris with mating surfaces and the mode of wear. It was found that cadmium worked as a solid lubricant and reduced wear and friction of the matrix alloy. © 1993.